Kubernetes bian cheng = Programming Kubernetes / = Programming Kubernetes - Hausenblas, Michael; Schimanski, Stefan (Zhongguo dian li chu ban she = China Electric Power Press Ltd., 2021)
Detailed summary in vernacular field.
880-04;O'Reilly Media Inc. shou quan chu ban. - Includes bibliographical references
Keywords: Kubernetes; Application software -- Development -- Computer programs; Application program interfaces (Computer software); Cloud computing; Open source software; Logiciels d'application; Développement; Logiciels; Interfaces de programmation d'applications; Infonuagique; Logiciels libres; APIs (interfaces)